Study of Prime, Pseudoprime and applications of Pseudoprime - et. al., A. Ananth Maria Pushpa, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The entire research paper is based on pseudoprime and their properties in the field of mathematics as well as the other fields. In this paper we will discuss about the properties and results of numbers and some of the applications of pseudoprime in computer application,Cryptography .